THE EFFECT OF COMPENSATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE DEWI SAMBI BATIK CRAFT CENTER - Desi Prasetiyani (Jurnal Multidisiplin Sahombu, 2023)
This study aims to examine and analyze the effect of compensation and work discipline on employee performance at Dewi Sambi Batik Craft Center. This type of research is quantitative research, data were collected from 80 respondents who were all employees at Dewi Sambi Batik Craft Center, the sampling method was saturated sampling, where all members of the population became the research sample. Data was collected by observation and questionnaire methods. The data collected was analyzed using multiple regression analysis with SPSS version 26. The results showed that compensation partially affected the performance of the Dewi Sambi Batik Krajinan Center employees, work discipline partially affected the employee performance of the Dewi Sambi Batik Krajinan Center. Compensation and work discipline simultaneously affect the performance of the Dewi Sambi Batik Krajinan Center employees